Semi-inclusive direct photon + jet and π0+jet correlations measured in p + p and central Au + Au collisions at √sNN=200 GeV - Aboona, Bassam; Deppner, Ingo Martin; Herrmann, Norbert; Leung, Yue; Söhngen, Yannick (Physical review, 2025)
The Solenoidal Tracker at RHIC (STAR) experiment at the Relativistic Heavy Ion Collider reports new measurements of jet quenching based on the semi-inclusive distribution of charged-particle jets recoiling from direct photon (𝛾dir) and neutral pion (𝜋0) triggers in 𝑝𝑝 and central Au+Au collisions at √𝑠𝑁⁢𝑁=200GeV for triggers in the range 9<𝐸trig𝑇<20GeV. The datasets have integrated luminosities of 3.9nb−1 for Au+Au and 23pb−1 for 𝑝𝑝 collisions. Jets are reconstructed using the anti-𝑘𝑇 algorithm with resolution parameters 𝑅=0.2 and 0.5. The large uncorrelated jet background in central Au+Au collisions is corrected using a mixed-event approach, which enables precise charged-particle jet measurements at low transverse momentum 𝑝ch𝑇,jet and large 𝑅. Recoil-jet distributions are reported in the range 𝑝ch𝑇,jet<25 GeV/𝑐. Comparison of the distributions measured in 𝑝𝑝 and Au+Au collisions reveals strong medium-induced jet yield suppression for 𝑅=0.2 with markedly less suppression for 𝑅=0.5. Comparison is also made to theoretical models incorporating jet quenching. These data provide new insight into the mechanisms underlying jet quenching and the angular dependence of medium-induced jet-energy transport and provide new constraints on modeling such effects.